Innovations in Developing HOTS IPAS Essay Questions for Fifth Grade Elementary School Students - Wicaksono, Adyatma Nugrahsanto; Faizah, Siti; Mardhatillah, Mardhatillah (Universitas Negeri Malang, 2025)
The development of High Order Thinking Skills (HOTS) questions in Science and Social Studies (IPAS) for fifth-grade elementary students is a crucial step toward improving education quality. These questions go beyond testing memory by fostering critical, analytical, and creative thinking skills aligned with modern educational demands. Employing the 3D model (Define, Design, Develop) the study systematically develops HOTS based questions tailored to learning objectives and student needs. The process integrates cognitive levels C4-C6 of Bloom's taxonomy, emphasizing analysis, evaluation, and creation to enhance higher-order thinking. Validation results show that these HOTS-based questions are